2016
DOI: 10.1099/ijsem.0.000907
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces arcticus sp. nov., isolated from frozen soil

Abstract: Actinomycete strain ZLN234 T was isolated from a frozen soil sample, which was collected from a glacier front in the Arctic. Chemotaxonomic and morphological characteristics were found to be typical of members of the genus Streptomyces. The strain formed a distinct phyletic line in the 16S rRNA gene tree and was closely related to Streptomyces olivochromogenes ATCC 3336 T (98.63 % similarity) and Streptomyces aureus B7319 T (98.56 %). Phylogenetic analysis based on the gyr B gene also showed clearly that strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…possess high adaptive capability for surviving in many extreme environmental conditions and their incidence had been documented in diverse extreme habitats including frozen soils, deserts, oceans, Arctic and Antarctic regions ( Maldonado et al, 2008 ; Le Roes-Hill et al, 2009 ; Malviya et al, 2009 ; Okoro et al, 2009 ; Ramesh and Mathivanan, 2009 ; Verma et al, 2009 ; Ivanova et al, 2010 ; Zothanpuia et al, 2018 ). Studies in frozen soils, Arctic and Antarctic regions had revealed a great diversity of cultivable Streptomyces species ( Le Roes-Hill et al, 2009 ; Ivanova et al, 2010 ; Li et al, 2011 ; Zhang et al, 2016b ; Kamjam et al, 2019 ), while in marine and deserts, Streptomyces spp. had been reported as one of the dominant culturable genera ( Okoro et al, 2009 ; Prieto-Davo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…possess high adaptive capability for surviving in many extreme environmental conditions and their incidence had been documented in diverse extreme habitats including frozen soils, deserts, oceans, Arctic and Antarctic regions ( Maldonado et al, 2008 ; Le Roes-Hill et al, 2009 ; Malviya et al, 2009 ; Okoro et al, 2009 ; Ramesh and Mathivanan, 2009 ; Verma et al, 2009 ; Ivanova et al, 2010 ; Zothanpuia et al, 2018 ). Studies in frozen soils, Arctic and Antarctic regions had revealed a great diversity of cultivable Streptomyces species ( Le Roes-Hill et al, 2009 ; Ivanova et al, 2010 ; Li et al, 2011 ; Zhang et al, 2016b ; Kamjam et al, 2019 ), while in marine and deserts, Streptomyces spp. had been reported as one of the dominant culturable genera ( Okoro et al, 2009 ; Prieto-Davo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological adaptations have enabled psychrophilic organisms to thrive in the polar regions, especially microorganisms which are high in number and usually uncharacterized [2,3,4,5]. However, when compared to the large number of polar microorganisms which have been reported, very few have been screened for the production of interesting secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Extremely low cold or cryoenvironment is an inexhaustible microbial habitat which has been emphasised by several studies in recent years [25, 26]. Because of significant climatic variables in extreme cold habitats, microbes inhabiting there can adapt to harsh conditions which can, in turn, produce novel compounds that are valuable for biotechnology applications [27].…”
Section: Extremely Low Cold or Cryoenvironmentmentioning
confidence: 99%
“…from the Antarctic ecosystem and other distinct studies requires to be investigated in such environmental sources [33, 34]. Likewise, recently published papers describe novel Streptomyces isolated from Arctic glacier [25, 26]. But, till date, no studies described yet concerning novel Streptomyces spp.…”
Section: Isolation Of Streptomyces From Cryoenvironmentsmentioning
confidence: 99%